Assisted dying requests from people in detention: Psychiatric, ethical, and legal considerations–A literature review - Franke, Irina; Urwyler, Thierry; Prüter-Schwarte, Christian (Frontiers in Psychiatry, 2022)
The principle of equivalence of care states that prisoners must have access to the same standard of health care as the general population. If, as recent decisions suggest, assisted dying is not limited to people with a terminal physical illness or irremediable suffering, it might also be requested by people with severe mental illness in long-term detention. Some of the countries with legal regulations on assisted dying also have recommendations on how to handle requests from prisoners. However, detention itself can lead to psychological distress and suicidality, so we must consider whether and how people in such settings can make autonomous decisions. Ethical conflicts arise with regard to an individual’s free will, right to life, and physical and personal integrity and to the right of a state to inflict punishment. Furthermore, people in prison often receive insufficient mental health care. In this review, we compare different practices for dealing with requests for assisted dying from people in prison and forensic psychiatric facilities and discuss the current ethical and psychiatric issues concerning assisted dying in such settings.